Production of bamboo leaf ash by auto-combustion for pozzolanic and sustainable use in cementitious matrices - Moraes, M. J.B. [UNESP] (2019)
In the context of world concern with the environment, this study aims to characterize an auto-combustion produced bamboo leaf ash (BLA) by its pozzolanic behaviour, reactivity and its influence in the total porosity, pore size distribution, tortuosity and mechanical behaviour of cementitious matrices. The chemical and physical characterization of the BLA was carried using X-ray fluorescence, determination of amorphous silica content, X-ray diffraction, Fourier Transform Infrared Spectrophotometry (FTIR), laser granulometry and field emission scanning electron microscopy (FESEM). The assessed BLA is a siliceous material (74.23%) with an amorphous nature due to the amorphous silica content, which represents 92.33% of the total silica. The BLA was classified as highly reactive by assessing its pH and conductivity in a saturated calcium hydroxide (CH) medium for different proportions and temperatures. Frattini analysis, the study of CH:BLA pastes (Thermogravimetric analysis and FTIR) and Portland cement (OPC)/pozzolan pastes (Thermogravimetric analysis and FESEM) are in agreement with this classification. The replacement of OPC by BLA improved the mechanical behaviour of the cementitious matrices, as well their durability. All the mortars containing BLA presented very similar compressive strength to a control mortar (100% OPC) after only 3 days of curing and at the following tested curing ages: 7, 28 and 90 days. In the mercury intrusion porosimetry analysis, the pastes with 20 and 30% BLA content presented higher tortuosity or fewer connected pores than the control paste. Thus, the auto-combustion method proved to be successful and BLA is a suitable alternative for sustainable high-performance matrices.